Daya Gabung dan Heterosis Galur Jagung (Zea mays L.) pada Karakter Hasil dan Komponen Hasil - setyowidianto, eko purnomo; Basuki, Nur; Damanhuri, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Corn productivity can be improved using hybrid varieties. Evaluation of inbreds and hybrids were required to obtain information of general combining ability and specific combining ability. The objective of this research was to find out inbred combining ability and hybrids heterosis from crosses of 10 inbreds (5 inbreds from PT. Agri Makmur Pertiwi and 5 introduced inbreds) based on yield and yield components character. Diallel mating design using method 2 model 1 of Griffing model and the testing were conducted from January to August 2012. The tests using a randomized block design with three replications. PWM-1 (PT. Agri Makmur Pertiwi group) and PWI-5 (introduced group) have GCA better than other inbreds on grain yield, ear length, ear diameter, number of seed rows, shelling percentage and 1,000 seeds weight. Hybrids PWM-5 x PWM-1, PWI-5 x PWM-1 and PWI-5 x PWM-5 have a positive SCA values and also inbred parent have a positive GCA value. Intercrosses of introduced group had the high heterosis for all characters. PWI-4 x PWI-2 had highest SCA and heterobeltiosis for ear diameter and 1,000 seeds weight, and for number of seed rows was PWI-5 x PWI-2.Keywords: diallel cross, heterobeltiosis